Computational Thinking and Coding for Kids Training for Elementary School Teachers - Dewi Indriati Hadi Putri; Taufik Ridwan; Nuur Wachid Abdul Majid; Hafiziani Eka Putri; Diky Zakaria; Yohanes Adi Nugroho (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2022)
Computational thinking and coding are thinking skills that are recently expected to be acquired by elementary school children as the era of the industrial revolution 4.0 requires students to be familiar with the use of technology. In some developed countries, the two skills have been included in elementary school curriculum. However, the situation is different in the context of Indonesia since teachers or instructors who are able to provide these skills are inadequate. Therefore, this training was intended to socialize and educate the application of coding and computational thinking, especially to elementary school teachers so that they have the ability to equip their students with those skills. The participants of this training were teachers of Labschool UPI Purwakarta. The training was conducted in one day containing the concepts and practices of ICT and computational thinking as well as coding for kids. The result of satisfaction questionnaire distributed to the participants after the training shows a good level of satisfaction in terms of training materials, delivery of materials, and the usefulness of activities as much as 71,4%, 57,1% and 92,9% consecutively. The teachers hope that follow-up trainings are carried out to increase their knowledge and ability in developing technology-based learning.